Good Corporate Governance toward Intellectual Capital - Muhammad Abdul Muis; Satria Adhitama (AFRE (Accounting and Financial Review), 2022)
This research aims to analyze the effect of the audit committee, board of directors, board of commissioners on intellectual capital in LQ-45 companies listed on the Indonesia Stock Exchange the period of 2016-2019. The results of this study indicate that partially the Audit Committee (KA) variable has a positive and significant influence on Intellectual Capital (IC). The variable of the Board of Directors (DD) has a negative but not significant effect on Intellectual Capital (IC). While the variable Board of Commissioners (DK) has a positive but not significant effect on Intellectual Capital (IC). Meanwhile, simultaneously the independent variables, namely the audit committee, the board of directors, and the board of commissioners, together have a positive and significant influence on the dependent variable, namely Intellectual Capital. The coefficient of determination of this study shows a number of 58.8% which indicates that the variation of the independent variable explains the rise or fall of the dependent variable, while the remaining 41.2% is explained by other independent variablesDOI: https://doi.org/10.26905/afr.v5i2.7809